Job rotation as a legal requirement: analysis of the acceptance and perception of bovin slaughter workers - Messias, Iracimara de Anchieta (2021)
This article presents an experience of a participative approach preliminary to the implementation of NR-36, which regulates work in meat and meat products companies. Although the norms provide for worker participation in the processes of implementing job rotation, they do not explain how to do it. The study was developed in the beef slaughtering sector using two complementary methods: observation of the work in loco, in order to select the jobs that are primarily eligible for the rotation, and a survey of the workers' perception of the level of acceptance of the rotation in the selected jobs. At first, 72% of the workers did not accept the rotation. After inclusion and participation in the implementation process, 86% of the workers in the dirty area and 64% in the clean area agreed to the rotation. As evidence of the advantages of the rotation, the variability in the work (30%), learning and gain of experience (40%), changes in movements (35%), and physical rest (32%) stand out. As disadvantages, the fear of accidents (30%) and the fear of change and of the unknown (25%) stand out. We conclude that the participatory approach preliminary to the changes in organizational design contributes to the understanding and perception of workers about the advantages and disadvantages of the rotation, indicating improvement of processes in compliance with legal requirements.